Markets in North Korea I: Development, structure, and changes - Moon-Soo Yang; Suk Lee (Korea Development Institute (KDI), 2022)
Over the past three decades, North Korea has experienced a period of economic change, most notably in the development of the market. North Korea maintains that it operates a tightly controlled planned economy, the elements of which are poorly understood by the international community. Currently, the economic system is supported by informal market activities that are the main source of income for the majority of ordinary economic players. Accordingly, economic researchers around the world have pivoted their focus toward the market activities in North Korea. In this issue of Dialogue, the KDI Office of North Korean Economic Studies invited Professor Moon-Soo Yang to share his knowledge on the basic elements of the North Korean market, directing particular attention to its unique development, structure, and recent changes. Professor Moon-Soo Yang is a leading researcher at the University of North Korean Studies, whose career has consistently dedicated focus to rigorous investigation and understanding of the North Korean market.
Keywords: 330; Marktwirtschaft; Marktmechanismus; Wirtschaftsgeschichte; Nordkorea